Structural and Dielectric Studies of Ni1−xAlxFe2O4 - Choudhary, Sunny; Singh, Deepanshi; Bhattarai, Mohan; Katiyar, Ram S.; Kumari, Poonam (Journal of Nepal Physical Society, 2023)
The nanoparticles of Ni1−xAlxFe2O4(x = 0,0.5) were synthesized via using sol-gel route and studied the structural and dielectric effect of aluminium content on Nickel site. The X-ray diffraction (XRD) revealed the single-phase cubic spinel structure of the parent compound. The lattice constant, volume, density, bond lengths, specific surface area and crystallite size were determined from the Rietveld refinement. In the Raman analysis, there are five active modes present in the synthesized samples. FTIR spectroscopy confirmed the formation of spinel ferrite and showed the characteristics absorption bands of metal oxygen (Fe-O) observed around 424-450 and 601-620 cm−1 corresponding to the stretching vibration frequency of the metal-oxygen at the octahedral site and tetrahedral site respectively. Dielectric behaviour showed that the value of dielectric constant (ε') and tangent loss (tanδ) decreases with frequency and confirmed the general behaviour of ferrites. The AC Conductivity (σac) was found lower in Ni0.5Al0.5Fe2O4 compared to NiFe2O4.